HW4-solutions - merino (aem2588) HW4 chen (55405) 1 This...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: merino (aem2588) HW4 chen (55405) 1 This print-out should have 20 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. 001 10.0 points Find the derivative of f when f ( x ) = sin x 2 + cos x . 1. f ( x ) = 2 cos x + sin 2 x (2 + cos x ) 2 2. f ( x ) = 2 cos x + 1 (2 + cos x ) 2 correct 3. f ( x ) = 2 cos x- 1 (2 + cos x ) 2 4. f ( x ) = 2 cos x- 1 2 + cos x 5. f ( x ) = 2 cos x + 1 2 + cos x Explanation: By the Quotient Rule, f ( x ) = cos x (2 + cos x ) + sin x sin x (2 + cos x ) 2 = 2 cos x + (cos 2 x + sin 2 x ) (2 + cos x ) 2 . But cos 2 x + sin 2 x = 1, so f ( x ) = 2 cos x + 1 (2 + cos x ) 2 . 002 10.0 points Find dy dx when x 3 y 3- y = x . 1. dy dx = 1- 3 x 3 y 3 3 x 3 y 2- 2 2. dy dx = 1 + 3 x 2 y 3 3 x 3 y 2- 2 3. dy dx = 1- 3 x 2 y 3 3 x 3 y 2- 1 correct 4. dy dx = 1- 2 x 3 y 3 2 x 3 y 2- 1 5. dy dx = 1- 3 x 3 y 2 3 x 2 y 2- 1 Explanation: Differentiating x 3 y 3- y = x implicitly with respect to x we see that 3 x 3 y 2 dy dx + 3 y 3 x 2- dy dx = 1 . Thus 3 x 3 y 2 dy dx- dy dx = 1- 3 x 2 y 3 and so dy dx = 1- 3 x 2 y 3 3 x 3 y 2- 1 . 003 10.0 points Determine f ( x ) when f ( x ) =- 4 x 7- 3 x 3- 9 . 1. f ( x ) =- 28 x 6- 9 x 2- 9 x 2. f ( x ) =- 28 x 6- 9 x 2- 9 3. f ( x ) =- 4 x 7- 9 x 2- 9 4. f ( x ) =- 28 x 6- 9 x 2 correct 5. f ( x ) =- 28 x 6- 3 x 3 Explanation: By linearity of differentiation and the rule ( x n ) = n x n 1 , merino (aem2588) HW4 chen (55405) 2 we see that f ( x ) =- 28 x 6- 9 x 2 . 004 10.0 points Find the derivative of f when f ( x ) = cos(sin x ) . 1. f ( x ) = sin x cos(cos x ) 2. f ( x ) =- cos x sin(cos x ) 3. f ( x ) = cos x sin(sin x ) 4. f ( x ) =- sin x cos(sin x ) 5. f ( x ) =- cos x sin(sin x ) correct 6. f ( x ) = sin x cos(sin x ) Explanation: Using the Chain Rule we see that f ( x ) = parenleftBig- sin(sin x ) parenrightBig (cos x ) =- cos x sin(sin x ) . 005 10.0 points Find dy/dx when 4 x 2 + 5 y 2 = 6 . 1. dy dx = 4 x 5 y 2. dy dx =- 4 xy 3. dy dx =- 4 x y 4. dy dx = x 5 y 5. dy dx =- 4 x 5 y correct 6. dy dx = 5 xy Explanation: Diferentiating 4 x 2 + 5 y 2 = 6 implicitly with respect to x we see that 8 x + 10 y dy dx = 0 . Consequently, dy dx =- 8 x 10 y =- 4 x 5 y ....
View Full Document

Page1 / 8

HW4-solutions - merino (aem2588) HW4 chen (55405) 1 This...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online